PERINATAL MORTALITY AND REGIONAL DIFFERENCES IN THE STATE OF PARANÁ, BRAZIL - Tereza Maria Mageroska Vieira; Rosana Rosseto de Oliveira; Verônica de Azevedo Mazza; Thais Aidar de Freitas Mathias (Universidade Federal do Paraná, 2015)
The aim of this study was to assess perinatal mortality in the state of Paraná by analyzing the total number of perinatal deaths among Paraná residents occurring between 1999 and 2010, as registered in the Mortality Information System and Stillborn Information System. This study calculated the differences between perinatal, fetal and early neonatal mortality coefficients from 1999 to 2001 and 2008 to 2010, according to data from regional health coordination centers. The results showed a 28.2% reduction in the perinatal mortality coefficient, 32.2% in the early neonatal coefficient and 25.2% in fetal mortality coefficient. Some highlights include a 8.8% increase in the early neonatal mortality rate reported by the 21st regional health coordination center, and the 5.9%, 12.3% and 12.2% increase in the fetal mortality coefficient in the 1st, 8th, and 16th regional centers. Even though the mean state perinatal mortality coefficient fell, high values persist in some regional health centers, pointing to the need for improving actions in prenatal and high-risk neonate care.